(3UMGaI GdGWaGd hGOHge (B/s - (3GdgjJj, gGOj fYeGfs ((3YeGf (B:s (3OGQ GSGeI ddfTQ h GdJhRjY ,s, 2012)
(3bSeJ gPg GdOQGSIGdi GHhGH h bSeJ cd HGH Gdi aUhd JfGhdJ aj GdHGH GdGhd LeghQ GOH GdGWaGd ef MjK NUGFUg h GSJLGHGJg ddGTcGd h GdeVGejf GdGOHjI h JfGhdJ aj GdHGH GdKGfj GOH GdGWaGd JYQjaG h fTGI h JfGhdJ aj GdHGH GdKGdK afhf GOH GdGWaGd h JfGhdJ aj GdHGH GdGNjQ hSGFW GdGWaGd Gdi GOHge h NUGFU cd hSjWs
Keywords: (3LeghQ GdGWaGd s; (3UMGaI GdGWaGd s; (3afhf GdGWaGd s; (3UMGaI s